MG-115 Compound heterozygous SCN4A mutation underlies severe congenital hypotonia and biophysical alteration in the encoded voltage-gated NAV1.4 sodium channel. (4th December 2015) - van Karnebeek, Clara DM; Ye, X Cynthia; Abdelsayed, Mena; Selby, Katherine; Zhang, Linhua; Chijiwa, Chieko; Hendson, Glenda; Sayson, Bryan; Gill, Harinder; Balicki, Martha; Eydoux, Patrice; Ross, Colin J; et al.
Abstract : Introduction: Mutations in the family of SCN genes encoding sodium channels are responsible for several disorders affecting the central and peripheral nervous systems and muscle. Disease arising from sodium channel mutants range from the relatively benign (e.g. mild myotonia) to the fatal (e.g. long-QT syndrome), with a wide variety of disorders spanning the spectrum of severity. Identified SCN4a mutations to date have been consistently autosomal dominant and associated with paramyotonia congenita, potassium-mediated periodic paralysis or aggravated myotonia due to defects altering the biophysical properties of sodium channels that mediate membrane hyper- or hypo-excitability. Here we describe a newly recognised autosomal-recessive syndrome comprising severe congenital hypotonia with respiratory failure in a family of Punjabi descent, with 2 of 3 children affected. Methods and results: Using whole exome sequencing we identified two new mutations (g. 62025363 C >T, D1069N and g. 62025425 T >G, splice site) in the SCN4A gene, confirmed via Sanger sequencing. Reverse transcriptase polymerase chain reaction shows that the splice-site mutation in SCN4A leads to altered RNA. To investigate the impact of the missense mutation, c.3205G >A, Chinese hamster ovary (CHOk1) cells transfected with either a WT or D1069N SCN4A were examined for their biophysical properties. A set of depolarizing test pulses was used to measure the voltage dependence of activation and indicated biophysical changes in the encoded voltage-gated sodium channel (NaV1.4). Conclusions: Together, our findings characterise the first reported evidence of an autosomal recessive SCN4a sodium channelopathy comprising severe congenital neuromuscular hypotonia and respiratory failure with biophysical dysfunction of NaV1.4 attributable to SCN4a compound heterozygous gene mutation.